Plasmodium matutinum Causing Avian Malaria in Lovebirds (Agapornis roseicollis) Hosted in an Italian Zoo - Cristiano Cocumelli; Manuela Iurescia; Elena Lavinia Diaconu; Valentina Galietta; Caterina Raso; Carmela Buccella; Fiorentino Stravino; Francesco Grande; Letizia Fiorucci; Claudio De Liberato; Andrea Caprioli; Antonio Battisti (Microorganisms, 2021)
Avian malaria is a worldwide distributed, vector-born disease of birds caused by parasites of the order Haemosporida. There is a lack of knowledge about the presence and pathogenetic role of Haemosporida in Psittacidae. Here we report a case of avian malaria infection in lovebirds (Agapornis roseicollis), with the genetic characterization of the Plasmodium species involved. The birds were hosted in a zoo located in Italy, where avian malaria cases in African penguins (Spheniscus demersus) were already reported. Animals (n = 11) were submitted for necropsy after sudden death and were subjected to further analyses including histopathology, bacteriology, and PCR for the research of haemosporidians. Clinical history, gross lesions and histopathological observation of schizonts, together with positive PCR results for Plasmodium spp., demonstrated that avian malaria was the cause of death for one animal and the possible cause of death for the other nine. The sequences obtained were compared using BLAST and analyzed for similarity to sequences available at the MalAvi database. Genetic analyses demonstrated a 100% nucleotide identity to Plasmodium matutinum LINN1 for all the obtained sequences. To our knowledge, this is the first report describing avian malaria in lovebirds.